2022
DOI: 10.3389/fimmu.2022.918140
|View full text |Cite
|
Sign up to set email alerts
|

The m6A/m5C/m1A Regulated Gene Signature Predicts the Prognosis and Correlates With the Immune Status of Hepatocellular Carcinoma

Abstract: RNA modification of m6A/m5C/m1A contributes to the occurrence and development of cancer. Consequently, this study aimed to investigate the functions of m6A/m5C/m1A regulated genes in the prognosis and immune microenvironment of hepatocellular carcinoma (HCC). The expression levels of 45 m6A/m5C/m1A regulated genes in HCC tissues were determined. The functional mechanisms and protein–protein interaction network of m6A/m5C/m1A regulated genes were investigated. The Cancer Genome Atlas (TCGA) HCC gene set was cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
58
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 39 publications
0
58
0
Order By: Relevance
“…As for the readers, ALYREF and YBX1 were remarkably overexpressed in GC patients. Research on bladder cancer, breast cancer, HCC, and oral squamous cell carcinoma revealed that ALYREF and YBX1 were upregulated as well ( 22 , 42 44 ). Intriguingly, high expression of ALYREF and YBX1 are also significantly correlated with the favorable prognosis of GC patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the readers, ALYREF and YBX1 were remarkably overexpressed in GC patients. Research on bladder cancer, breast cancer, HCC, and oral squamous cell carcinoma revealed that ALYREF and YBX1 were upregulated as well ( 22 , 42 44 ). Intriguingly, high expression of ALYREF and YBX1 are also significantly correlated with the favorable prognosis of GC patients.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies validate that the dynamic modification of m 5 C and its regulators is involved in a series of physiological and pathological processes, including RNA stability, gene expression, and protein synthesis. As for tumor malignant biological behaviors, it has been reported that m 5 C and its regulators play essential roles in the pathogenesis of leukemia ( 21 ), hepatocellular carcinoma (HCC) ( 22 ), glioblastoma multiforme (GBM) ( 12 ), and bladder cancer ( 20 ), indicating the promising prospect of m 5 C modification in cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro and in vivo tumor growth, invasion, migration, and the epithelial-mesenchymal transition of cancer cells are all influenced by dynamic RNA methylation and modification events, such as m 6 A, m 1 A, m 5 C and m 7 G (X. Y. Li et al, 2022 ; Traube et al, 2017 ). In addition to playing essential roles in various cancers and anticancer effects, modification events can also be used as prognostic indicators ( Mahmoud and Ali, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Variations in mRNA transcriptomes between different methylation subtypes were strongly linked with biological pathways involved in MRG and the immune system ( Gu et al, 2021 ; X. Y. Li et al, 2022 ). We determined two gene subtypes relied on the DEGs between the two methylation subtypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation